2022
DOI: 10.3389/fmicb.2021.781275
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel Microbiome-Based Biomarker of Post-antibiotic Dysbiosis and Subsequent Restoration

Abstract: Background: The human gut microbiota are important to health and wellness, and disrupted microbiota homeostasis, or “dysbiosis,” can cause or contribute to many gastrointestinal disease states. Dysbiosis can be caused by many factors, most notably antibiotic treatment. To correct dysbiosis and restore healthier microbiota, several investigational microbiota-based live biotherapeutic products (LBPs) are in formal clinical development. To better guide and refine LBP development and to better understand and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…The emergence of LCA and DCA and other 7-dehyroxylated derivatives (12-KLCA, DHLCA, isoLCA, 3-KDCA) starting on day 7 post-baseline revealed that commensals with 7-dehydroxylating activity were being restored over time in rCDI patients after RBX2660 treatment. Consistent with this, the restoration of secondary BAs post-baseline coincided with a shift to a healthier MHI-A in the same cohort(8,11). Notably, a healthier MHI-A is partially defined by increased relative operational taxonomic units (OTUs) from the Clostridia class, which is known to harbor critical commensals that express 7-dehydroxylating genes(35).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The emergence of LCA and DCA and other 7-dehyroxylated derivatives (12-KLCA, DHLCA, isoLCA, 3-KDCA) starting on day 7 post-baseline revealed that commensals with 7-dehydroxylating activity were being restored over time in rCDI patients after RBX2660 treatment. Consistent with this, the restoration of secondary BAs post-baseline coincided with a shift to a healthier MHI-A in the same cohort(8,11). Notably, a healthier MHI-A is partially defined by increased relative operational taxonomic units (OTUs) from the Clostridia class, which is known to harbor critical commensals that express 7-dehydroxylating genes(35).…”
Section: Discussionsupporting
confidence: 70%
“…The copyright holder for this preprint this version posted September 1, 2022. ; https://doi.org/10.1101/2022.08.30.22278604 doi: medRxiv preprint diversity (7)(8)(9)(10). The analysis conducted on samples from these trials also led to the development of the Microbiome Health Index (MHI-A)-a microbiome-based biomarker of antibiotic-induced dysbiosis and restoration (11). RBX2660 treatment is associated with a significant shift of MHI-A to levels associated with those observed in healthy subjects (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another, called the Microbiome Health Index (MHI), considers bacterial distributions within the Firmicutes, Bacteroidetes, and Proteobacteria phyla. MHI, evaluated after antibiotic exposure, is measured by the relative abundances of bacteria belonging to the Clostridia (Firmicutes phylum) and Bacteroidia (Bacteroidetes phylum) classes, given their associations with healthy functions, compared with the abundances of Bacilli (Firmicutes phylum) and Gammaproteobacteria (Proteobacteria phylum), given their association with pathogenesis 24 …”
Section: Resultsmentioning
confidence: 99%
“… 16 , 17 Broadly, studies demonstrate that a healthy gut microbiota is dominated by a diversity of members from the Bacteroidetes and Firmicutes phyla, with a lower abundance of Proteobacteria and Actinobacteria. 16 , 18 Genera such as Lactobacillus , Bacillus , Clostridium , and Ruminococcus within the Firmicutes phylum and Bacteroides and Prevotella within the Bacteroidetes phylum are frequently associated with good health. 16 , 19 Because interindividual variation in the types of genera and species in the human gut occurs, 19 21 providing a specific definition of what constitutes a healthy microbiota is complicated.…”
Section: Introductionmentioning
confidence: 99%